2017
DOI: 10.1590/1676-0611-bn-2017-0323
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of ants and mites in the diet of the Brazilian frog Chiasmocleis leucosticta (Anura: Microhylidae)

Abstract: We describe here the diet of the microhylid frog Chiasmocleis leucosticta based on the stomach contents of 72 individuals (47 males and 25 females) collected in pitfall traps at the Reserva Florestal de Morro Grande, state of São Paulo, southeastern Brazil. We identified 1,981 food items distributed in 13 prey categories of arthropods, mainly ants, mites and collembolans. Formicidae was the most abundant and frequent prey category, including 16 genera from seven subfamilies, and data on ant availability in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Similar results, with ants being the most consumed prey, were found for different species of the genus as Chiasmocleis capixaba (Van Sluys et al 2006), C. albopunctata (Araújo et al 2009), C. alagoanus (Leite-Filho et al 2017), C. leucosticta (Lopes et al 2017), C. hudsoni and C. shudikarensis (Silva et al 2019). Also, within Microhylidae, similar patterns were found for other species of this family, always revealing large frequencies of occurrence and high relative importance indices for Formicidae (Erftemeijer and Boeadi 1991;Hirai and Matsui 2000;Solé et al 2002;Berazategui et al 2007).…”
Section: Discussionsupporting
confidence: 65%
“…Similar results, with ants being the most consumed prey, were found for different species of the genus as Chiasmocleis capixaba (Van Sluys et al 2006), C. albopunctata (Araújo et al 2009), C. alagoanus (Leite-Filho et al 2017), C. leucosticta (Lopes et al 2017), C. hudsoni and C. shudikarensis (Silva et al 2019). Also, within Microhylidae, similar patterns were found for other species of this family, always revealing large frequencies of occurrence and high relative importance indices for Formicidae (Erftemeijer and Boeadi 1991;Hirai and Matsui 2000;Solé et al 2002;Berazategui et al 2007).…”
Section: Discussionsupporting
confidence: 65%
“…Trueb and Gans (1983) suggested that, at least in Rhinophrynus (which lacks mentomeckelians), the contraction of the supplementary elements (referred by them as m. mandibulomentalis) would raise the floor of the mouth, contributing to the lingual protraction. It is interesting to note that in both Rhinophrynidae, and Brevicipitidae + Hemisotidae (the two groups where the anterolateral supplementary elements are more hypertrophied, forming a fusiform belly) the protraction of the tongue occurs through "hydrostatic extension", a highly sophisticated mechanism that is present only in these families and in Microhylidae, most of which are specialized myrmecophages (Lopes et al, 2017;Channing and R€ odel, 2019;Sah et al, 2019). This mechanism consists of a relatively slow but highly accurate projection of the tongue enabled by a unique muscle, the m. genioglossus dorsoventralis, only present in these clades (Trueb and Gans, 1983;Nishikawa, 2000;Meyers et al, 2004;Monroy and Nishikawa, 2009).…”
Section: A Functional Enigmamentioning
confidence: 99%
“…Most anurans are considered generalist consumers because they feed on a wide prey ran e D e man and r eb o and dder o ever t ere is evidence t at some of them have a narrow diet, showing a specialized consumption on certain biological groups (Agudelo-Cantero et al 2015, Lopes et al 2017, Araujo-Vieira et al 2018. Differences in the diet composition have been related to different factors, which may be extrinsic, such as the site traits (Bonansea and Vaira 2007), competition (Duellman and Trueb 1994), or seasonality (Berazategui et al 2007), which can offer different food resources, or intrinsic factors, s c as onto enetic c an es itfie d and Donnelly 2006), reproductive behavior, and sex (Lamb 1984, Maneyro et al 2004, which in ence t e n tritiona re irements of an rans Both extrinsic and intrinsic factors are related to the use of food resources and the variation in the diet composition between and within species (Lima and Magnusson 2000).…”
Section: Introductionmentioning
confidence: 99%